Management practices in high-tech environments - Jemielniak, Dariusz; Kociatkiewicz, Jerzy; Gale Group (Hershey, Penn. Information Science Reference, 2008)
Presents research on management practices in American, European, Asian and Middle-Eastern high-tech companies, with particular focus on fieldwork-driven, but reflective, contributions.
Preface -- Acknowledgment -- Section I. The high-tech workplace -- Section II. The knowledge worker -- Section III. Workplace relations and power -- Section IV. Self management -- Compilation of references -- About the contributors -- Index.
Electronic reproduction.
Keywords: High technology industries -- Management; Information technology -- Management; Knowledge workers -- Management; Electronic books